NnSR1, a class III non-S-RNase constitutively expressed in styles,isinducedin roots and stems under phosphate deficiency in Nicotiana alata - Rojas, Hernan Javier (2013)
Background and Aims: Non-S-ribonucleases (non-S-RNases) are class III T2 RNases constitutively expressed in styles of species with S-RNase-based self-incompatibility. So far, no function has been attributed to these RNases. The aim of this work is to examine if NnSR1, a non-S-RNase from Nicotiana alata, is induced under conditions of phosphate (Pi) deprivation. The hypothesisisthat under Pi-limited conditions, non-S-RNase functions may resemble the role of S-like RNases. To date, the only RNases reported to be induced by Pi deficiency are class I and class II S-like RNases, which are phylogenetically different from the class III clade of RNases. Methods: Gene and protein expression of NnSR1 were assayed in plants grown hydroponically with and without Pi, by combining RT-PCR, immunoblot and enzymatic activity approaches. Key Results: NnSR1 transcripts were detected in roots 7 d after Pi deprivation and remained stable for several days. Transcript expression was correlated based on Pi availability in the culture medium. Antiserum against a peptide based on a hypervariable domain of NnSR1 recognized NnSR1 in roots and stems but not leaves exposed to Pi shortage. NnSR1 was not detected in culture medium and was pelleted with the microsomal fraction, suggesting that it was membrane-associated or included in large compartments. The anti-NnSR1 inhibited selectively the enzymatic activity of a 31-kDa RNase indicating that NnSR1 was induced in an enzymatically active form. Conclusions: The induction of NnSR1 indicates that there is a general recruitment of all classes of T2 RNases in response to Pi shortage. NnSR1 appears to have regained ancestral functions of class III RNases related to strategies to cope with Pi limitation and also possibly with other environmental challenges. This constitutes the first report for a specific function of class III RNases other than S-RNases.